Anti-epileptic drug intake adherence: the value of the blood drug level measurement and the clinical approach Aderência à ingestão de medicamentos antiepilépticos: o valor da avaliação dos níveis sanguíneos e a abordagem clínica - MARLEIDE DA MOTA GOMES; HEBER DE SOUZA MAIA FILHO; ROSÂNGELA APARECIDA MARTINS NOÉ (Arquivos de Neuro-Psiquiatria, 1998)
It was evaluated the patient antiepileptic drug (AED) intake adherence in a pilot cross-sectional study carried out at a neurologic out-patient clinic of a university hospital. Ninety-three AED blood concentration (phenobarbital, phenytoin, carbamazepine) were analyzed from 24 patients. The variability of the AED blood level was measured (in the steady state period by means of the variation coefficient) and compared with the self-reported antiepileptic medication non-adherence, AED blood level according to the range (therapeutic or not), and the seizure control. It was not observed any strong correlation between the higher value of variability and the other three parameters of no adherence. The highest correlation was with the blood drug level (therapeutic or not). The evaluation of blood drug measurement alone, except in cases of extreme low adherence and variability of drug intake, is not enough for the recognition of incorrect drug intake, but the clinical markers and the self-reported adherence have to be also considered for this sort of evaluation. Avaliou-se a aderência à ingesta de drogas antiepilépticas (DAE) em estudo piloto transversal conduzido em ambulatório de hospital neurológico universitário. Noventa e três amostras sanguíneas com concentraço de DAE (fenobarbital, fenitoína, carbamazepina) foram analisadas de 24 pacientes. A variabilidade dos níveis sanguíneos das DAE (em estado estável - steady state period, analizada por meio do coeficiente de variação) foi comparada com a auto-referida não aderência à ingesta da DAE, níveis sanguíneos das DAE de acordo com a faixa (terapêutica ou não) e o controle das crises epilépticas. Não foi observada correlação forte entre o maior valor da variabilidade e os outros três parâmetros de aderência, apesar da maior correlação com o nível sanguíneo (terapêutico ou não). A avaliação do nível sérico isolado, exceto em caso de extrema baixa aderência e variabilidade da ingesta das DAE, não é suficiente para o reconhecimento da ingesta inadequada, mas os marcadores clínicos e a auto-aderência referida também têm que ser consideradas para esse tipo de avaliação.